Secular and nationalist Jinnah - Javed, Ajeet (Oxford ; New York : Oxford University Press, 2009)
Political biography of Mohammed Ali Jinnah, 1876-1948, statesman and founder of Pakistan.
Originally published: New Delhi : Kitab Pub. House, 1997.
Includes bibliographical references and index.
Keywords: Jinnah, Mahomed Ali, -- 1876-1948.; Prime ministers -- Pakistan -- Biography; India -- Politics and government -- 1919-1947.